Kyl-Kobyz and related musical instruments of central Asian Turkic peoples - Saule I. Utegalieva, Maksat S. Medeubek,; Bassykara, Yersaiyn; Medeubek, Sagatbek M.; Tokzhanov, Tulepbergen (Opción, 2020)
This article is for the first time devoted to a comparative-typological study of related bowed instruments such as Kyl-Kobyz, Kyl-Kyyak, Kobuz, which were distributed among the Turkic peoples of mainly Central Asia and adjacent territories of Eurasia. As a result, the main function of the kylkobyz instrument is associated with shamans. Among Kazakhs, shamans reached the XX century. In conclusion, the issue of not losing the traditional theme in the modern world is very important. Research in this direction will help preserve the traditional features of the stringed instruments of the Turkic peoples of Central Asia.